In vitro induction of enamel subsurface demineralization for evaluation of diagnostic imaging methods - Rívea Inês Ferreira; Francisco Haiter-Neto; Cínthia Pereira Machado Tabchoury; Frab Norberto Bóscolo (University of São Paulo, 2007)
The aim of this study was to investigate a model of inducing enamel subsurface demineralization for evaluating diagnostic imaging methods. Fifty sound teeth had their crowns coated with acid-resistant varnish, leaving a 7 mm² circular window of exposed enamel in one of the proximal surfaces. The specimens were assigned to 5 groups (4 experimental and the control) and were kept immersed in a buffer solution at pH 4.8, 50% saturated in relation to enamel, for 60, 75, 90 and 120 days, or were not exposed to the solution. Digital radiographs were taken, prior to and after each immersion period, and interpreted by a radiologist. For validation, the enamel was submitted to microhardness profiling. In addition, the solutions were analyzed for phosphorus (Pi) and calcium (Ca) concentrations. Microhardness data were evaluated using two-way ANOVA (p<0.05) and Tukey's test. Pi and Ca concentrations were compared using one-way ANOVA (alpha = 0.05). The performance of radiography was assessed by ROC analysis. The microhardness values for the control group ranged from 405 to 432 KHN. Of the 4 experimental groups, the 60-day group demonstrated the highest values (179-379 KHN) and the 120-day group, the lowest values (103-277 KHN). The lowest total concentrations of Pi and Ca (1.74 mM and 2.63 mM, respectively) were found in the solutions of the 60-day group, indicating the lowest rate of mineral loss, however, there was no significant difference among the other experimental groups. The performance for detecting images consistent with caries lesions was high (Az = 0.89). Therefore, this in vitro model of inducing demineralization may be considered suitable for research intended to evaluate imaging methods for the diagnosis of proximal caries lesions.